LEGAL PROTECTION AGAINST VICTIMS OF VERBAL SEXUAL HARASSMENT (CATCALLING) IN THE CRIMINAL ACT OF SEXUAL VIOLENCE: PERLINDUNGAN HUKUM TERHADAP KORBAN PELECEHAN SEKSUAL SECARA VERBAL (CATCALLING) DALAM UNDANG-UNDANG TINDAK PIDANA KEKERASAN SEKSUAL - Hia, Septatinus (UPMI Proceeding Series, 2023)
This study aims to analyze the concept of verbal sexual harassment (catcalling) in Indonesian criminal law and legal protection for victims of verbal sexual harassment (catcalling) in the TPKS Law. The research method used in this research is normative research. Based on the results of the research on the concept of verbal sexual harassment (catcalling), people commit sexual acts: non-physically aimed at the body’s sexual desires and/or reproductive organs with the intention of degrading a person’s dignity based on their sexuality and/or decency. Legal protection for victims of sexual harassment. verbally (catcalling) in the TPKS Law, namely the right to get protection from violence and the right to be free from treatment that degrades his dignity. The form of protection is in the form of fulfilling rights and providing assistance to provide a sense of security to victims which must be carried out by LPSK or other institutions in accordance with the provisions of the legislation.